From job competencies to humanity-centric education: a new imperative for transforming higher education - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Across the world, universities have long been driven by a predominant goal, that is to produce graduates who are ready for the workforce. Teaching and learning processes are geared toward measurable learning outcomes, mainly the job skills, competencies, and attributes aligned with employability. While this focus has value, it also reveals a critical blind spot, in that it only stands as an education designed primarily to serve the economy and often neglects the deeper human need to become whole, relational, ethical, and reflective individuals. Preparing students to function as workers is not the same as preparing them to thrive as human beings who can relate meaningfully with others, act responsibly toward their environment, and live with inner balance and purpose. For decades, many universities have centered their mission on producing graduates who are "workforce-ready." Curricula, assessments, and learning outcomes largely emphasize work skills, job competencies, and attributes aligned with economic demands. While this approach has material value, it reveals a deeper concern, that the education system has become focused on economic survival rather than insaniyyah (human wholeness). As a result, it risks neglecting the development of individuals as ethical, reflective, and relational servants of God who capable of contributing to social harmony and moral upliftment.